TerjemahanÊ¾Ä›lÅhÃ®m dan YehwÄh - Milton Pardosi (Jurnal Koinonia, 2014)
Ê¾Ä›lÅhÃ®m(elohim) and Ê¾ÇŽdÅnÄy (adonay)are titles of the being or element who is worshiped by human beings in the Old Testament.Â  Old Testament writers used these two words which refer to the being or element that is worshiped by Israel and pagan nations.Â  The context of the words itself will determine whether the being or element who is worshiped is the One who created the heavens and earth (Gen. 1 and 2; Exod. 20:11) or not.Â  If it is yes, the translation in Indonesian is Allah or Tuhan (English: God or Lord), but if not, it will be allah or tuhan (English: god or lord). YehwÄh (Yahweh) is the Name of Ê¾Ä›lÅhÃ®m (elohim)or ÇŽdÅnÄy (adonay)who created the heavens and the earth (Gen. 1 and 2; Exod. 20:11).Â  Names in the Hebrew Bible are never translated.Â  Then, no need to translate the word YehwÄh (Yahweh)into TUHAN or ALLAH (English: LORD or GOD), on the contrary, it should be left alone or just make its transliteration: YAHWEH or YAH or YEHWAH.